Effectiveness of Direct Village Fund Cash Assistance in Pulau Tiga Village, Pulau Tiga Barat District, Natuna Regency, 2020 - Muhammadiah, Muhammadiah; Herdiana, Dian; Persada, Razaki (Jurnal Pendidikan Indonesia, 2024)
Direct Cash Assistance (BLT) is a social assistance program from the government which aims to provide direct financial assistance to people in need. This research aims to find out and assess the effectiveness of Direct Village Fund Cash Assistance (BLT-DD), analyze the impact of Direct Village Fund Cash Assistance on the community receiving aid and analyze the Government’s policy regarding Direct Village Fund Cash Assistance (BLT-DD) in Pulau Tiga Village, Pulau Tiga Barat District, Natuna Regency. This research uses qualitative methods with data collection methods of observation, interviews and documentation. The informants in this research consisted of 12 people. The results of the research show that (1) The Government’s policy regarding Direct Village Fund Cash Assistance (BLT-DD) in Pulau Tiga Village, Pulau Tiga Barat District, Natuna Regency is to implement strengthening public outreach and communication, increasing transparency and accountability, optimizing the use of resources, and strengthening monitoring and evaluation. (2) The effectiveness of direct cash assistance from Village Funds in Pulau Tiga Village, Pulau Tiga Barat District, Natuna Regency in 2020 can be measured by several aspects, namely accuracy in timing, accuracy in calculating costs, accuracy in measurements, accuracy in making choices, accuracy in thinking, accuracy in carrying out orders, accuracy in determining goals and accuracy of targets. (3) The impact of direct cash assistance from village funds on aid recipient communities in Pulau Tiga Village, Pulau Tiga Barat District, Natuna Regency refers to the speed of distribution and direct benefits, reducing financial burdens and increasing skills and economic opportunities.